Peer interaction in dental materials in FOUNLP - Sala, Alicia (2012)
The paper corresponds to a research project on peer learning in dental education in FOUNLP There is now a very present idea on the importance of peer work in vocational college. Explore, explain, inform, investigate, are fundamental activities to build learning and this is further strengthened when we put into play in situations of peer interaction.